CARBON AND NITROGEN ISOTOPE SYSTEMATICS WITHIN A SECTOR-GROWTH DIAMOND FROM THE MIR KIMBERLITE, YAKUTIA - Bulanova G.P.; Pearson D.G.; Hauri E.H.; Griffin B.J. (My University, 2002)
A single Yakutian octahedral diamond, displaying striking internal growth structure whereby cubic and octahedral growth sectors are inter-grown and surrounded by an octahedral rim, has been analysed for carbon and nitrogen isotopic compositions (by secondary ion mass spectrometry, SIMS), and for nitrogen concentration (by SIMS and Fourier transform infrared spectroscopy, FTIR) and nitrogen aggregation state (by FTIR). A graphite “seed” inclusion identified within the diamond is enriched in K, Ca, Ti, Rb, and Sr, providing evidence that the diamond may have grown from a carbonate melt/fluid interacting with upper mantle rocks. Carbon and nitrogen isotope compositions become progressively heavier from the core region (δ13C=−7‰ to −5‰ and δ15N=−3‰) towards the inner rim zones (δ13C=−3‰ and δ15N=+8.9‰ to +5‰) of the diamond. Nitrogen concentration and aggregation measurements show corresponding decreases that generally correlate with the isotopic variation. These systematic changes within the core and intermediate regions of the diamond are consistent with their formation during diamond growth from CO2-rich fluids as a continuous event, accompanied by slight progressive isotopic fractionation of carbon and nitrogen. However, the observed isotope and nitrogen abundance trends differ from those predicted from thermodynamic modelling of fluid–solid equilibria in a C–N–O–H-bearing system due to changes in parameters such as fO2.